THE IMPACT ASSESSMENT OF RURAL DEVELOPMENT PROGRAM: CASE ON COMMUNAL CATTLE IN KULWARU VILLAGE, SPECIAL REGION OF YOGYAKARTA - Santosa, Fajar Julian; Setyowati, Retno; Wibowo, Agung (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2024)
This study aims to assess the social, economic, and environmental impacts of rural development programs, namely PNPM, in the case of building communal cattle. This qualitative research was conducted in Kulwaru Village, Yogyakarta Special Region Province. Data was collected from 15 informants, including the communal cattle group, local government, and related community figures. The data collected was then analyzed using Miles and Huberman interactive data analysis, including data condensation, data presentation, and conclusion. The results of the research show that (1) The construction of communal cattle provides changes in the social aspect, namely by increasing public awareness of environmental cleanliness, growing the spirit of cooperation, and mutual trust in the management of communal cattle, resulting in a decrease in crime in Kulwaru Village; (2) In the environmental aspect, there are changes in several aspects including settlements and the environment are more organized, pollution from wells is reduced, there are no flooding problems, resulting in safer public health and livestock; (3) In the economic aspect, communal cattle have an impact on several things, including increasing livestock productivity, ease of health checks, easy access to credit, and the processing of livestock manure waste into fertilizer with profitable value. This study recommends to stakeholders the importance of development programs tailored to local needs and potential as a viable strategy for sustainable rural development.Keywords: Communal Cattle, Impact Assessment, Rural Development, PNPM, Special Region Of Yogyakarta.